Revision de la técnica de la evaluación ultrasonografica de la reserva ovarica mediante el recuento de folículos antrales y el volumen ovarico promedio - Carpio-Guzmán, Luis Alberto (2019)
The asseessment of ovarian reserve is one of the cornerstones of the diagnosis of the infertile couple. The measurement of follicle stimulating hormone (FSH) has been considered the gold standard for such assessment, however ultrasonographic evaluation (antral follicle count and ovarian volume average) is an alternative that has advantages for its low cost and easily reproducible from technical point of view. The aim of this paper is to review and publicize the ultrasound technique of assessing ovarian reserve in order to unify criteria for implementation in hospitals.